Pembelajaran Agama Kristen Berbasis Pengalaman: Membangun Iman Melalui Narasi Hidup - Rangga, Oktavianus (PEADA': Jurnal Pendidikan Kristen, 2024)
This article discusses an experiential Christian learning model that aims to build students' faith through a life narrative approach. This method utilizes real stories and personal experiences to help students internalize Christian values ​​and understand biblical teachings more deeply. The research was conducted using a qualitative approach, through literature studies and narrative content analysis from various sources, books and journal articles related to this method. The results show that the use of narratives in learning can enrich students' understanding of faith, encourage personal reflection, and strengthen community ties through group discussions. However, this approach also faces challenges, such as the diversity of students' experiences that can affect the way they live out Christian values. The active role of teachers as facilitators is needed to ensure that learning remains focused and in accordance with biblical principles. This article emphasizes that the experiential learning model can make a significant contribution to Christian religious education, especially in creating a more relevant, contextual, and transformative learning process in the modern era.